Roadmap towards N‐Heterocyclic [2.2]Paracyclophanes and Their Application in Asymmetric Catalysis. Issue 27 (2nd August 2013) - Busch, Mark; Cayir, Merve; Nieger, Martin; Thiel, Werner R.; Bräse, Stefan
Abstract: A novel family of [2.2]paracyclophane derivatives is described. Different substituted pyrazole, triazole and pyrimidine moieties were introduced to the [2.2]paracyclophane scaffold and the products were characterized spectroscopically and by X‐ray structure analysis. These compounds are promising ligands for application in asymmetric catalysis. We show here that one of these ligands can catalyze asymmetric conjugate addition. Furthermore a palladium complex was synthesized by using a hydroxy‐pyrazolyl[2.2]paracyclophane ligand. Abstract : Herein we describe the synthesis of a novel family of [2.2]paracyclophane derivatives, whereby pyrazole, triazole and pyrimidine moieties with different substituents were introduced to the [2.2]paracyclophane scaffold. The motivation for this work was the synthesis of promising ligands for application in asymmetric catalysis. We show that one of these ligands can catalyze asymmetric conjugate addition.